2022
DOI: 10.3390/ijerph19031303
|View full text |Cite
|
Sign up to set email alerts
|

Reprotoxic Impact of Environment, Diet, and Behavior

Abstract: Reproductive health is progressively declining due to multiples endogenous and exogenous factors, such as environmental contaminants, diet and behavior. Accumulated evidences confirm that fertility and reproductive function have been adversely affected by exposure to chemical contaminants released in the environment. Today, the impact of diet and behavior on reproductive processes is also receiving special attention from the scientific community. Indeed, a close relationship between diet and fertility has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 196 publications
0
6
0
Order By: Relevance
“…Some EDCs have a genotoxic effect, causing deoxyguanosine hydroxylation and/or DNA strand breaks (both single and double), thereby promoting the malignant transformation of affected cells. Numerous endogenous and exogenous factors, such as environmental pollution and diet lead to the deterioration of the reproductive health of individuals of all links of the food chain [3,14,15].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some EDCs have a genotoxic effect, causing deoxyguanosine hydroxylation and/or DNA strand breaks (both single and double), thereby promoting the malignant transformation of affected cells. Numerous endogenous and exogenous factors, such as environmental pollution and diet lead to the deterioration of the reproductive health of individuals of all links of the food chain [3,14,15].…”
Section: Resultsmentioning
confidence: 99%
“…The first stage occurs during vitogenesis when maternal cortisol is incorporated into the yolk, and the second stage occurs during maturation and ovulation, when cortisol can play a regulatory role, causing maturation [21]. It has been shown that the stress-induced increase in cortisol, associated with a decrease in estradiol, affects the functions of granulosa cells in the follicle, worsening the quality of oocytes [15]. Recent studies suggest that this hormone may act as a key factor linking the stimuli of the social environment and the onset of sex change, initiating the transition in steroidogenesis from estrogen to androgen.…”
Section: Resultsmentioning
confidence: 99%
“… 39 In Western countries, Westernized dietary habits, stress, and environmental pollution have been reported to affect reproductive function. 40 Lifestyle changes, including alcohol consumption and smoking status may exert intricate effects, potentially contributing to the increasing prevalence of infertility. Understanding these factors is crucial for developing preventive and therapeutic strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Different mechanisms are involved, depending on the nature of the stressor. Many chemicals are also known to lead to reprotoxicity, in particular, endocrine disruptors ( 36 , 37 ).…”
Section: Common Health Targets Of Chemicals and Climate Change-relate...mentioning
confidence: 99%